2020
DOI: 10.1139/er-2020-0032
|View full text |Cite
|
Sign up to set email alerts
|

Increasing importance of climate change and other threats to at-risk species in Canada

Abstract: In a previous analysis, six major threats to at-risk species in Canada were quantified: habitat loss, introduced species, over-exploitation, pollution, native species interactions and natural causes (Venter et al. 2006). Because of rapid environmental change in Canada, and an enhanced understanding of the drivers of species endangerment, we updated the 2005 analysis, and tested for changes in threats up until the end of 2018. We also expanded the scope to acknowledge climate change as a seventh major threat to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 337 publications
0
31
0
Order By: Relevance
“…Considering the threats that affect biodiversity most globally (Maxwell et al 2016) and within Canada (Woo-Durand et al 2020), I sought to develop a human footprint map incorporating threats with the most up to date layers. Although I did address parts of the three 'big killers' for global biodiversity -Over-exploitation with logging, Agricultural Activity and Urban Development (Maxwell et al 2016), I was unable to include introduced species that affect 46% of Canada's "at-risk" species and many aspects of habitat loss and overexploitation (Woo-Durand et al 2020). Even though habitat loss from seismic lines and recreation trails could be seen with high resolution imagery in my validation plots, there were no national spatial datasets that could be applied.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Considering the threats that affect biodiversity most globally (Maxwell et al 2016) and within Canada (Woo-Durand et al 2020), I sought to develop a human footprint map incorporating threats with the most up to date layers. Although I did address parts of the three 'big killers' for global biodiversity -Over-exploitation with logging, Agricultural Activity and Urban Development (Maxwell et al 2016), I was unable to include introduced species that affect 46% of Canada's "at-risk" species and many aspects of habitat loss and overexploitation (Woo-Durand et al 2020). Even though habitat loss from seismic lines and recreation trails could be seen with high resolution imagery in my validation plots, there were no national spatial datasets that could be applied.…”
Section: Resultsmentioning
confidence: 99%
“…COSEWIC identified that species classified as "at-risk" in Canada are most commonly affected by the threat of habitat loss, affecting over 80% of species included (Venter et al 2006;Woo-Durand et al 2020). I mapped nine threats that directly contributed to habitat loss for the Canadian human footprint to help address the threat that most commonly affects Canadian biodiversity "at-risk".…”
Section: Threats To Biodiversitymentioning
confidence: 99%
See 3 more Smart Citations